Prognostic factors for mortality in children with severe dengue: A single-centre retrospective cohort study - Lidwina Elisabeth Setiana Salombe; Nurnaningsih; Surya Adhi; Eggi Arguni (Heliyon)
Background: Severe dengue is a serious manifestation of dengue infection and one of the causes of death in children. Recognizing the prognostic factors for death in severe dengue, based on the 2009 WHO guidelines, can help provide appropriate management to reduce the death rate. Objective: To determine the prognostic factors for mortality in pediatric patients with severe dengue admitted to Dr. Sardjito General Hospital, Yogyakarta. Methods: We retrospectively collected data on children with severe dengue from January 2017 to December 2022 at Dr. Sardjito Hospital. Bivariate and multivariate analyses were performed to determine the prognostic factors that significantly impacted the outcome of death. Results: There were 120 eligible patients with severe dengue during the study period; 17 subjects (14.2 %) died and 103 subjects (85.8 %) survived. Multivariate analysis showed that mechanical ventilation (RR 8.97, 95 % CI 1.31–103.21, p 0.025), fluid overload >10 % (RR 7.56, 95 % CI 1.15–49.72, p-value = 0.035), and vasoactive-inotropic score (VIS) ≥13.75 (RR 13.56, 95 % CI 1.78–103.21 p-value = 0.012) were the prognostic factors for mortality in pediatric patients with severe dengue. Conclusion: Mechanical ventilation, excess fluid and the need for multiple vasoactive drugs are the prognostic factors for mortality in severe dengue in children.